A faster algorithm to compute the visibility map of a 1.5D terrain - Loffler, Maarten (2018)
Given a 1.5D terrain, i.e., an x-monotone polygonal line in R 2 with n vertices, and 1 ≤ m ≤ n viewpoints placed on some of the terrain vertices, we study the problem of computing the parts of the terrain that are visible from at least one of the viewpoints. We present an algorithm that runs in O(n + m log m) time. This improves over a previous algorithm recently proposed.